(untitled) (SCIENCE TIME JOURNAL, 2026)
Sports injuries are among the most common health problems affecting professional athletes and can significantly influence athletic performance, physical function, and career longevity. This article examines the most frequently encountered sports injuries among professional athletes an analyzes modern rehabilitation approaches used for recovery and return to sports participation. The study is based on a review of contemporary scientific literature related to sports medicine, injury prevention, diagnosis, and rehabilitation. Particular attention is given to muscle strains, ligament sprains, tendon injuries, fractures, and joint disorders. The article discusses the importance of early diagnosis, appropriate medical intervention, and structured rehabilitation programs in restoring physica function and preventing recurrent injuries. Modern rehabilitation methods, including therapeutic exercise, physiotherapy, functional training, and multidisciplinary rehabilitation strategies, are evaluated. The findings indicate that comprehensive rehabilitation programs improve mobility, muscular strength, coordination, and overall athletic performance.